EFFICACY OF (TrND14) ON SEED GERMINATION AND SEEDLING VIGOUR OF CHICKPEA TRICHODERMA ASPERELLUM (Journal of Plant Disease Sciences, 2024)
Chickpea (Cicer arietinum L.) is one of the most important rabi season legume crop belonging to family Fabaceae. The present study investigated the effect of T. asperellum (TrND14) on seed germination and seedling vigour of chickpea under In vivo conditions. The JG-62 variety of chickpea was used for seed treatment. Among all the treatments T6 i.e. T. asperellum TrND14 (2% WP) @ 20g/kg showed highest percent seed germination (82.72 %) and seedling vigour index (2373.23) which was followed by T5 - T. asperellum TrND14 (2% WP @16g/kg) showing percent germination (82.46 %) and seedling vigour (2314.65) as compared to control. Also,T6i.e. T. asperellum (TrND14) (2% WP) @ 20g/kg showed highest yield attributing characters of chickpea as compared to control, which was followed by T5 - T. asperellum (TrND14) 2% WP @16g/kg. Thus T. asperellum (TrND14) can be used for seedtreatment to chickpea for growthpromotion.
Keywords: Chickpea; T. asperellum Seed germination; Seedling vigour